A new krypton complex – experimental and computational investigation of the krypton sulphur pentafluoride cation, [KrSF5]+, in the gas phase. Issue 23 (7th June 2022) - Oliveira, Sandrina; Bandeira, Nuno A. G.; Leal, João P.; Maria, Leonor; Carretas, José M.; Monteiro, Bernardo; Marçalo, Joaquim
Abstract : Gas-phase reaction of Kr + with SF6, examined by FTICR mass spectrometry, gave rise to the new species [KrSF5 ] +, whereas a Xe analogue was not observed. Ab initio computational studies established [KrSF5 ] + as a weakly bound complex. Abstract : The gas-phase reactions of noble gas (Ng) cations, namely Kr + and Xe +, with SF6 were investigated experimentally by Fourier transform ion cyclotron resonance mass spectrometry and computationally using RI-MP2 and BCCD(T) methods. The study revealed a new interaction between Kr + and neutral SF6 that gave rise to a new cationic, weakly bound complex of Kr, [KrSF5 ] +, although the major reaction channel was dissociative electron transfer to yield SF5 + and {Kr, F}. Experimental studies examined the formation and stability of the new species and computational studies addressed the energetics of the reaction and indicated that [KrSF5 ] + is stable by ca. 1 kcal mol −1 . The same computational approach was used to examine the reaction of Xe + with SF6 and showed it to be thermodynamically unfavourable by ca. 35 kcal mol −1, confirming the non-observation of reaction in the mass spectrometry experiments. An analysis of the bonding in [KrSF5 ] + clearly showed that it is a non-covalently bound species, while in its presumed precursor [KrSF6 ] + a partially covalent Kr–F bond is present.